THE GAP BETWEEN VOCABULARY KNOWLEDGE AND READING COMPREHENSION IN A FOREIGN LANGUAGE - Calixto, Benedito José (Revista Expectativa, 2007)
Assuming that children present a vocabulary knowledge about 5000 to 7000 words of their mother tongue before they have instructions at school, leads us to suppose what would be the circumstances in relation to the acquisition of a foreign language. Learner can face as major complexity as lesser be his/her vocabulary knowledge in the target language. The majority of the students took English classes in the elementary schools, as a result it can be suppose that the amount of vocabulary knowledge may not be enough to reach a satisfactory reading comprehension of most of the texts in a higher education level. It is taking into account all of a background and the proposed programs as well. Reading can be considered the most used and necessary skill in Brazil, consequently it is assumed that there is a major gap to be achieved on foreign language reading researches in view of the amount of researches done on the native language.